Asymmetric Magnetoelectrochemistry: An Efficient Method to Grow Enantiopure Self-Assemble Monolayer - Suryakant Mishra; Debkumar Bhowmick (Magnetochemistry, 2020)
In this work, we are presenting magnetic field dependent electrochemical method to grow enantiopure monolayer. Thiol gold monolayer formation by redox reaction is studied on gold coated ferromagnetic surface. Infrared and photoemission spectroscopies are used to probe the quality of the monolayers, grown using different direction of magnetization of surface. Commercially available chiral molecules, L-cysteine along with dsDNA are used as control molecules for the measurements. Since it is established by aligning the electron spin within the surface, it helps to adsorb specific enantiomer of molecules, we have shown how direction of the magnet helps to grow good quality monolayer. Potential application of this work is in improving quality of monolayer and chiral separation.